PENGATURAN SANKSI PIDANA TERHADAP KORPORASI SEBAGAI PELAKU TINDAK PIDANA PERIKANAN BERDASARKAN UNDANG-UNDANG NOMOR 31 TAHUN 2004 JUNCTO UNDANG-UNDANG NOMOR 45 TAHUN 2009 TENTANG PERIKANAN - Victor Silalahi; Mukhlis R; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Recognition of corporations as subjects in criminal offenses in the fishery sector is contained in Article 101 of Law Number 31 of 2004, Juncto of Law Number 45 of 2009 concerning Fisheries which states that, in the event that the criminal acts referred to in this law are carried out by corporations , criminal charges and penalties imposed on the management and criminal penalties plus 1/3 (one third) of the criminal sentences. In this law the criminal target is only aimed at the management only, while the corporation cannot be sentenced. Such an arrangement will cause many weaknesses, Logically, for certain cases where the profits derived by the company are so great and / or the losses incurred by the community are so great, the imposition of imprisonment / fines "only" to the management will be out of proportion. The type of research used by the author is normative legal research that examines the principles of law, namely the principle of strict liability. The type of data used in this study is to use secondary data, namely primary legal materials (the 1945 Constitution, Laws, Maritime Affairs and Fisheries Ministerial Regulations, Government Regulations), secondary data (books relating to research results, namely the regulation of sanctions crimes against corporations as perpetrators of fisheries crime, legal journals, and legal theory), and tertiary legal materials (legal dictionaries and the internet. From the results of this study it can be concluded that the imposition of criminal sanctions only on the management alone in a fishery crime committed by a corporation is ineffective and is not sufficient to provide a guarantee that the corporation will not repeat its actions in the future. This is because the sanctions in the fisheries law are not comparable with the actions carried out by the corporation, where if there is a criminal offense in the fishery sector carried out by the corporation it will result in losses for the community such as small fishermen as well as losses against the state. The author's suggestion, first should be in the fisheries law, against corporations as perpetrators of crime, criminal sanctions imposed on the corporation, not just its managers. secondly, lawmakers are expected to formulate a fisheries law whose material contains criminal sanctions against the corporation, not just the management.Keywords: Criminal Sanctions–Corporate–Criminal Act-Fisheries